The Depoliticisation and 'ASEANisation' of Counter-Terrorism Policies in South-East Asia: A Weak Trigger for a Fragmented Version of Human Security - Alfred Gerstl (ASEAS - Austrian Journal of South-East Asian Studies, 2010)
This article applies a modified version of the theoretical approach of the Copenhagen School to demonstrate that the Association of Southeast Asian Nations (ASEAN) has since 2001 reacted in a twofold way to the complex political obstacles to closer counter-terrorism co-operation: First, it has responded with securitising terrorism as a transnational crime and, second, with a depoliticisation and ‘ASEANisation’ of its counter-terrorism policies. Depoliticisation and ‘ASEANisation’, i.e. the framing of a security threat under the ASEAN Way values, are both deliberate political actions. They enable politicians to base co-operation among the ASEAN members and with outside powers on a non-political, technical basis. Contradicting an assumption of the Copenhagen School, this study argues that in South-East Asia where sovereignty and non- interference are still core principles this approach can offer better political opportunities to resolve a security threat than a ‘classic’ securitisation. Furthermore, this article demonstrates that ASEAN’s anti-terrorism policies reflect its fragmented version of human security, which is based on national and regime rather than individual security. As counter-terrorism does not enjoy political priority in the region, these policies can only be a weak trigger for the implementation of ASEAN’s notion of human security. ----- Dieser Artikel wendet eine leicht modifizierte Version der Copenhagen School an, um aufzuzeigen, wie die Vereinigung südostasiatischer Nationen (ASEAN) seit 2001 auf die vielfältigen politischen Hindernisse für eine engere regionale Anti-Terrorismus-Zusammenarbeit reagiert hat. ASEAN hat, erstens, eine Sekuritisierung des Terrorismus als transnationales Verbrechen und, zweitens, eine Depolitisierung und „ASEANisierung“ (die Kontextualisierung einer sicherheitspolitischen Bedrohung unter den Werten des ASEAN Way) ihrer Anti-Terrorismus-Politik vorgenommen. Sowohl Depolitisierung und „ASEANisierung“ sind bewusste politische Handlungen, die es den PolitikerInnen ermöglichen, die interne wie externe Zusammenarbeit auf eine unpolitische, technische Basis zu gründen. Im Widerspruch zu einer These der Copenhagen School wird hier argumentiert, dass ein solcher Ansatz in Südostasien, wo Souveränität und Nicht-Einmischung immer noch zentrale Prinzipien sind, realpolitisch bessere Chancen eröffnen kann, um ein sicherheitspolitisches Problem zu bewältigen als eine „klassische“ Sekuritisierung. Zusätzlich zeigt der Artikel, dass ASEANs Anti-Terrorismus-Ansatz das fragmentierte Verständnis der Organisation in Bezug auf menschliche Sicherheit widerspiegelt. Dieses basiert stärker auf nationaler und Regime- als auch auf individueller Sicherheit. Da Anti-Terrorismus-Politik in der Region jedoch keine Priorität genießt, ist diese Politik bloß eine schwache Triebfeder für die Implementierung von ASEANs Verständnis von menschlicher Sicherheit.